2021
DOI: 10.33654/math.v7i1.1146
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical logical intelligences as a predictor of mathematics learning outcomes

Abstract: Penelitian ini dimaksudkan guna mengetahui prediksi hasil belajar matematika siswa mengacu dari kecerdasan logis matematis serta kecerdasan visual spasial. Penelitian ini menerapkan pendekatan kuantitatif, jenis penelitian korelasional. Penelitian dilaksanakan di SMP Negeri 16 Yogyakarta. Sampel yang digunakan sebanyak 36 siswa, metode penentuan sampel memakai cluster random sampling. Adapun instrumen yang dipakai guna menghimpun data yaitu skala kecerdasan logis matematis serta visual spasial. Teknik analisis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
1
1
0
1
Order By: Relevance
“…This result is in line with several studies that have also found a positive effect of logical-mathematical intelligence on problem-solving ability (Asmal, 2020;Azinar et al, 2020;Etchepare et al, 2011;Zulkarnain & Nurbiati;. This type of intelligence plays an important role in one's mathematical ability (Estri & Ibrahim, 2021;Sukardjo & Yusdiningtias, 2018). In essence, this intelligence is indeed standardized as a parameter of achievement of abilities in the field of mathematics (Dara & Budiarto, 2018;Putri, 2018).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This result is in line with several studies that have also found a positive effect of logical-mathematical intelligence on problem-solving ability (Asmal, 2020;Azinar et al, 2020;Etchepare et al, 2011;Zulkarnain & Nurbiati;. This type of intelligence plays an important role in one's mathematical ability (Estri & Ibrahim, 2021;Sukardjo & Yusdiningtias, 2018). In essence, this intelligence is indeed standardized as a parameter of achievement of abilities in the field of mathematics (Dara & Budiarto, 2018;Putri, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…For example, the ability to hypothesize plays an important role in planning solutions and making decisions about the type of problem solution. In addition, mathematical problems certainly require various mathematical calculation skills, which is also part of logical-mathematical intelligence (Estri & Ibrahim, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Basri, Tayeb, Abrar, Nur, & Angriani (2020) menemukan dalam penelitiannya di salah satu SMP di Sulawesi Selatan bahwa hasil belajar matematika siswa masih pada kategori rendah, yaitu hanya 70% dari 81 siswa belum mencapai nilai KKM 75. Hal ini diperkuat temuan lebih dari lima penelitian dalam durasi 2017 hingga 2020 yang mengungkapkan bahwa hasil belajar matematika masih pada kategori rendan atau tidak memuaskan (Estri & Ibrahim, 2021). Ini artinya ada faktor-faktor yang memengaruhi hasil belajar matematika yang perlu dioptimalkan.…”
Section: Pendahuluanunclassified